Public finance and taxation inequality in the municipalities of Boyacá, 1985-2010 - Guerrero, Plinio Atanael Guerrero (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Inequality in tax revenue per capita for municipalities and provinces of the department of Boyacá and its evolution, is analyzed using three indicators (Gini, Theil and sigma factor), for approaching to the explanation of the contribution of taxation decentralization process in the reduction of inter municipal and provincial disparities. The results suggest that in tax matters there is a process of convergence, moreover, to contrast them with indicators such as the NBI, the percentage of population in poverty and the Gini expenditure by municipality, in 1993 and 2005, the latter presented important decreases that somehow confirm the improvement in the taxation equity indicators.